PENGARUH IKLIM ORGANISASI, KEDISPLINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA MELALUI EFIKASI DIRI PT ISS CABANG SOUTH QUARTER JAKARTA SELATAN - Muhammad Nur Ali; Reinardus Dwi Prio Christianto (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2026)
Muhammad Nur Ali: The Influence of Organizational Climate, Discipline and Work Environment on Performance Through Self-Efficacy of PT ISS South Quarter Branch, South Jakarta. The purpose of this research is to determine the influence of organizational climate, discipline and work environment on performance through self-efficacy of PT ISS Indonesia South Quarter Branch, South Jakarta. The method in this research is survey research with a quantitative approach, assessment based on numbers using statistical calculations, using Saturated Sampling/census techniques. This research used a sample of 114 employees. Data was processed using the SEM, Smart PLS, 3.0 method.The research results show that the Organizational Climate variable (X1) directly has no effect on Self-Efficacy (Z), Discipline (X2) directly has a significant positive effect on Self-Efficacy (Z), Work Environment (X3) directly has no effect on Self-Efficacy ( Z), Organizational Climate (X1) and, Discipline (X2) do not directly have a significant positive effect on Performance (Y), Work Environment (X3) directly has a positive and significant effect on Performance (Y), and Self-Efficacy (Z) directly does not directly have a significant effect on Performance (Y) at PT ISS South Quarter Branch, South Jakarta.